PERAN CORPORATE SOCIAL RESPONSIBILITY DALAM MEMBANGUN CITRA PERUSAHAAN: SEBUAH LITERATUR - Andi Devy Aisyah Ansar; Indah Putri Nurafifah; Sri Sundari; Afdal Madein (Jurnal Akuntansi dan Bisnis, 2023)
Corporate Social Responsibility (CSR) has become an important part of the corporate landscape. CSR can also be used as a strategy to create and enhance the company's image. There are many bad effects related to damage when the company does not heed the social, economic, and environmental responsibilities, in which the company operates. If this damage can be minimized by carrying out social responsibility in the form of CSR programs and the program can improve the company's reputation then what is the next role of CSR in improving the company's image? By using the Literature Review method, the results obtained by the author are the implementation of the CSR programs which has become one of the most important drivers of the company's reputation. The CSR programs carried out are in accordance with the CSR principles that are sustainable, accountable and transparent. In addition, it also enhances the reputation and credibility of the company. The results of this moderation show how important it is for reputable business companies to consider CSR as the main factor influencing organizational commitment.